Current Trends and Issues Involving Screen Time and Physical Activity Engagement Among School Students: A Thematic Review - Victor Fello Piores; Roxana Dev Omar Dev; Mohd Mokhtar Muhamad; Dharatun Nissa Puad Mohd Kari (OVS LLC, 2023)
Study purpose. Physical inactivity and excessive screen time engagement among school-aged children is a global issue which is known to be linked with sedentary lifestyle. Several studies were conducted about sedentary behavior among children, but still lacking is a review paper that analyzes the current trends and issues on physical inactivity and excessive screen time. This study aims to identify the current issues and trends on physical activity and screen time among school students discussed in the articles published from 2018-2022. Materials and methods. Quantitative and qualitative methods were used in this study. Quantitative approach was used to explain the trends and statistics in terms of literatures geographical dissemination and specified topic or themes developed within the period from 2018 to 2022. Qualitative approach was implemented to establish patterns and themes. This study generates themes and patterns from the articles published from 2018 to 2022. Thirty articles were included via database searched from SCOPUS, SportsDiscus and PubMed.gov. Thematic analysis was done using ATLAS.ti 22. Results. Five main themes were generated: 1) behavioral impact; 2) engagement level: age and gender specific; 3) association to socio-economic status; 4) impact on adiposity; and 5) school curriculum role. Conclusions. Excessive screen time and physical inactivity have a diverse effect on young populations health. Understanding the patterns and themes generated in this study will be of great help in terms of designing a program of activity that will counter measure the negative effect associated with sedentary lifestyle.